Communication Design of Bureaccratic Organizations in Gender Perspective in the Government of South Tapanuli District - Elfi Yanti Ritonga; Syukur Kholil; Hasan Sazali (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to describe the communication design of bureaucratic organizations from a gender perspective in the South Tapanuli Regency Government.This research is a type of research qualitative descriptive. The data collection techniques used were observation and interviews. The results showed that: (1) the communication design of bureaucratic organizations in a gender perspective in the South Tapanuli Regency Government is structured and runs well, communication is established through programs that have been made,the regional secretary liaises with the heads of offices, the head of the office deals with staff from the district head and sub-district offices, the sub-district head with the village then the village head with the community, (2)Organizational communication is carried out in the form of meetings such as coordinating tasks to solve problems, (3) organizational communication designs in the form of written and oral regulations in implementing work programs to achieve goals, (4) work motivation, there are rewards given to employees and punishment when making mistakes and there is no difference in the treatment of attitudes and communication towards men and women, (5) the recruitment system in structural positions is based on ability, there is no nepotism and strict selection, the recruitment of honorary employees is adjusted to the needs of the field and educational background, (6) bureaucracy in a gender perspective In the South Tapanuli Regency Government there is no difference between men and women, including to become leaders and this is done democratically.